The Effect of the Strategy of Accelerating Thinking on the Achievement of Arabic Grammar for First-Year Middle School Female Students - Hammadi , Hassan (Al-Adab Journal, 2024)
The current research aims to identify the “effect of the strategy of accelerating thinking on the achievement of Arabic grammar for first-year middle school female students”. To achieve this, the researcher adopted an experimental design with partial control, which is the control group design with a post-test. The researcher intentionally chooses (Al-Yasmine Intermediate School for Girls) affiliated with the Baghdad Al-Rusafa Directorate/First. The number of classes of the first intermediate in this school was two classes. The researcher chooses, through random drawing: the experimental group, (40) female students, who studied Arabic grammar using the strategy of accelerating thinking. The other represented: the control group, (40) female students, who studied according to the traditional method. After the researcher determined the scientific material that he hoped to teach in the experiment, the researcher formulated the behavioral objectives, and their number in the final form reached (51) behavioral objectives. The researcher prepared the teaching plans, and models of them were presented to experts and shaped in their final form.The researcher formulated the paragraphs of his test and presented them to experts to choose what suits his research and modify what needs to be modified to represent the research tool. In light of that, the researcher prepared a test to measure the achievement of the Arabic grammar subject consisting of (25) paragraphs in three questions of the type (multiple choice, put in meaningful sentences, and true or false) distributed over the six levels of Bloom's cognitive taxonomy. After applying the experiment that lasted a full semester, the researcher applied the tool to the research sample, and he used several statistical methods, including: the t-test for two independent samples to analyze the variance. The study yielded the following result: The students of the experimental group outperformed the students of the control group in the achievement of the Arabic grammar subject, and the differences were statistically significant between the students of the two groups (experimental and control).The most important conclusions drawn by the researcher were:The superiority of thinking acceleration strategy over the traditional method in increasing the achievement of Arabic grammar among first-year middle school students.The effectiveness of teaching increases with the thinking acceleration strategy in academic subjects with a hierarchical structure (of information), including Arabic grammar.In light of the results and conclusions made by the researcher, recommendations can be put forward, including:Adopting the strategy of accelerating thinking in teaching Arabic grammar, to reorganize the learned material with what is in the previous cognitive structure of the learners.The necessity of training teachers of Arabic grammar on the strategy of accelerating thinking and introducing them to training courses while they are in work.The researcher suggested a number of suggestions that would complement his research, including:Applying this study on other academic stages.Applying this study to show the effect of its independent variable according to the gender variable.